(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the experiences and attitudes of health professionals towards cultural diversity in their teams? Purpose: The purpose of the herewith study was to examine cultural diversity in nursing teams and all the circumstances that shape the area of work within culturally diverse healthcare teams. The aim of the study was to explore the experiences gathered by healthcare professionals and their attitudes towards cultural diversity in healthcare teams. Method: The method used in this research was a qualitative approach. Data were gathered through semi-structured individual interviews conducted with nine healthcare professionals, selected by purposive sampling. The first part of the questions covered demographic characteristics, such as age, gender, level of education, workplace, length of service and nationality. The second part of the questions asked was about how health workers accept the cultural diversity of their colleagues and where they see obstacles and possible improvements. The data were analyzed using the content analysis method. Results: Two themes were developed using the text analysis method: (1) cultural diversity in healthcare teams; and (2) the desire to develop cultural competences in healthcare teams. Organization: The results showed that interpersonal relationships in healthcare teams are good, but also suggested that stereotypes are present in the background. Organizations should pay more attention to multicultural education. Society: In a global world, it is impossible to avoid cultural diversity. As a result, it is crucial for people to develop awareness, knowledge and skills when it comes to working and living with other cultures. Originality: In our review of Slovenian and foreign literature, we did not find much research on cultural diversity in healthcare teams. Limitations/Future Research: As far as limitations of the survey is concerned, we need to stress the fact that it covered a very small sample of participants, and as such under-represented different levels of the health system. As a consequence, the results cannot be generalized to the whole health system. Another limitation of the study is the lack of foreign and especially domestic research on cultural diversity in nursing teams. It would be sensible to conduct another research using a quantitative research paradigm and thus cover all levels of the healthcare system in Slovenia. This approach would provide a broader insight into where and why intercultural barriers occur in nursing teams.